Influence of background oxygen pressure on film properties of pulsed laser deposited Y:BaZrO3 - Bae, Kiho; Jang, Dong Young; Choi, Sung Min; Kim, Byung-Kook; Lee, Jong-Ho; Son, Ji-Won; Shim, Joon Hyung (ELSEVIER SCIENCE SA, 2014)
Yttrium-doped barium zirconate (Y:BaZrO3, BZY) thin films were prepared using pulsed laser deposition (PLD) on MgO substrates at 700 degrees C by varying the ambient oxygen pressure. The microstructure and electrical properties were then investigated using transmission electron microscopy and electrochemical impedance spectroscopy. Dense, well-crystallized BZY films were produced at ambient oxygen pressures (P-amb,P-o2) of <= 6.67 Pa. At P-amb,P- (2)(o) = 13.3 Pa, conical amorphous defects and porous microstructures were observed in the films. The conductivity of PLD BZY prepared at P-amb,P-o2 <= 13.3 Pa was measured to be close to that of reference polycrystalline BZY films, and the grain-boundary properties governed the overall ion conduction, with nano-grains being covered by the space charge depletion zones. At P-amb,P-o2 >= 13.3 Pa, microstructural defects significantly degraded the electrical properties. (C) 2013 Elsevier B.V. All rights reserved.
Keywords: DOPED BARIUM ZIRCONATE; OXIDE FUEL-CELLS; PROTON CONDUCTION; GRAIN-BOUNDARIES; THIN-FILMS; ELECTRICAL-CONDUCTIVITY; ELECTROLYTE; IMPEDANCE; MICROSTRUCTURES; CERAMICS